The effect of behavioral biases and gender differences on portfolio returns & investment decisions: An experimental approach - El Kashef, Noran Naiem (AUC Knowledge Fountain, 2017)
This thesis examines the effect of risk attitude, confidence and optimism behavioral biases on investment decisions and portfolio returns. The thesis methodology utilizes an experimental approach, whereby students compete through a semester long stock market simulation using the Stock-Trak simulation platform. Behavioral biases are examined through a behavioral biases diagnostic assessment completed by students during the trading period. Findings of this study show that both confidence and optimism biases have statistically significant impact on investors’ decisions and consequently affect investors’ portfolio returns. Findings also show that high confidence levels have positive impact on portfolio returns, on the other side, portfolio optimism bias, has a negative impact on portfolio returns. Data also suggests that males who are found to be more optimistic tend to lose more than less optimistic males in the sample. Another finding in this study shows that gender is the only highly statistically significant variable that predicts and explains investors risk attitude.